2020
DOI: 10.1080/19932820.2020.1768024
|View full text |Cite
|
Sign up to set email alerts
|

Effects of music therapy on occupational stress and burn-out risk of operating room staff

Abstract: The operating theatre staff is exposed to various constraints such as excessive working hours, severe medical conditions and dreadful consequences in case of malpractice. These working conditions may lead to high and chronic levels of stress, which can interfere with medical staff well-being and patients quality of care. The aim of this study is toassess the impact of music therapy on stress levels and burnout risk on the operating room staff. This is a preexperimental study including the operating rooms staff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 58 publications
1
19
0
2
Order By: Relevance
“…The present study's brief burnout intervention was received extremely well and the majority of participants reported that the session was helpful, even participants who did not report emotionally challenging work, caring for passed patients, or the presence of burnout, which supports implementation of burnout interventions for HCWs prior to experiencing significant burnout symptoms. These findings align with previous research that found music therapy 10 and chaplain interaction 11 for HCWs to benefit wellbeing and discourage burnout. This study also agrees with the findings of Schoenborn et al, 13 who found a memorial service for patient death to be beneficial for resident physicians.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The present study's brief burnout intervention was received extremely well and the majority of participants reported that the session was helpful, even participants who did not report emotionally challenging work, caring for passed patients, or the presence of burnout, which supports implementation of burnout interventions for HCWs prior to experiencing significant burnout symptoms. These findings align with previous research that found music therapy 10 and chaplain interaction 11 for HCWs to benefit wellbeing and discourage burnout. This study also agrees with the findings of Schoenborn et al, 13 who found a memorial service for patient death to be beneficial for resident physicians.…”
Section: Discussionsupporting
confidence: 91%
“…Further, Kacem et al 10 found music therapy to be a simple, noninvasive strategy that significantly reduced burnout for HCWs. Given the heavy workload and lack of downtime of HCWs, burnout prevention strategies that include music may be especially feasible.…”
mentioning
confidence: 99%
“…Out of 685 articles, only 13 addressed the use of musical therapy in organizations. Furthermore, the few empiric studies that are similar to this one, on an experimental basis and which checked the efficacy of musical therapy to reduce the level of stress in health care professionals, were carried out in other geographical contexts, such as Tunisia, Northern Africa (Kacem et al, 2020), or Florida, in the United States of America (Wenzel, 2018).…”
mentioning
confidence: 99%
“…Significant attention has been paid to the transmission of trauma, vicarious traumatic stress, burnout, and compassion fatigue among therapists and community workers ( Clements-Cortes, 2013 ; Fairchild, 2018 ; Downs, 2019 ). The literature even highlights how the creative arts therapies can be a resource for health workers in the face of burnout ( Kacem et al, 2020 ; Reed et al, 2020 ). Again, however, I point to the ways in which these can be understood as individualized rather than collective struggles.…”
Section: Trauma Under Neoliberalism and The Problem With “Resilience”mentioning
confidence: 99%